Metsäteollisuudenvähähiilisyystiekartantaloudelliset vaikutukset; The Low-carbon Roadmap of the Finnish Forest Industries: An Economic Impact Assessment - Jussi Lintunen; Jyrki Ali-Yrkkö; Martti Kulvik (The Research Institute of the Finnish Economy (ETLA), 2020)
– In this paper, we analyse the economic impacts of the low-carbon roadmap made for the Finnish forest indus-tries. The analysis is based on a future scenario provid-ed by AFRY. Given the unit prices and production levels of six forest industry production categories, we assess the value added and employment effects to the Finnish economy. If the scenario is fulfilled, the change would be stark compared to the developments in the previous decades. The value added of forest industries would in-crease 55-75% from 2017 to 2035 and 90-135% from 2017 to 2050. The indirect effects through the value chains would be of similar magnitude. If the develop-ment of labour productivity would remain at recently ob-served levels, the increased forest industry production would maintain the current employment leve
Keywords: L6; L73; Q01; 330; Forest industry; Climate change; Low carbon; Impact; Value added; Employment